External Quality Assessment in Laboratory Safety Area (PNAEQ-1S Segurança Laboratorial) - Ventura, Catarina (2023)
Introduction: The National External Quality Assessment Program (PNAEQ) provides tools for carrying out external quality assessment in Laboratory Safety area, since 2010. These tools have changed over the years, but all of them allow the identification of occurrences and/or critical points in the operation, installations or equipment, that could have impact on the safety of patients and workers, beyond prioritize the necessary improvement actions. Aims: Presentation of data and methodology implemented in PNAEQ since 2010, for the External Quality Assessment (EQA) in Laboratory Safety area.